EFEK SENAM PERSADIA SERI PERTAMA TERHADAP LINGKAR PINGGANG DAN KADAR TRIGLISERIDA DARAH PADA WANITA USIA REPRODUKTIF NON DIABETES - Hariyanto, Olivia Ramadhanty; Purwanto, Bambang; Andriati, Andriati (Universitas Tribhuwana Tunggadewi, 2021)
Hypertriglyceridemia along with an elevated waist circumference is the best predictor for diabetes in women. In Indonesia, the prevalence of diabetes in women is high enough that it needs prevention. The first Persadia exercise can be done to modify plasma triglycerides and waist circumference. This research was conducted to attest the effectiveness of the first Persadia exercise on waist circumference and plasma triglycerides in non-diabetic women of reproductive age. The design of this research is Quasi Experiment with a one-group pretest-posttest approach involving 12 from 20 women who matched the criteria. The data obtained were analyzed through the descriptive statistical test, normality test, and paired sample t-test. The mean decrease in waist circumference was 1,167±2,29 cm (p-value = 0.105), While the mean decrease in plasma TG was 9,083±39,69 mg/dL (p-value=0.445). Based on these results, it can be concluded that the first Persadia exercise did not significantly improve waist circumference and plasma triglycerides in non-diabetic women of reproductive age. Further research needs to be carried out by adding subject variations, increasing the duration of exercise, and controlling the subject’s nutritional intake to validate the research.